Non-Kinetic Operations as a Tool of Strategic Pressure: Case Studies of Finland and Poland - Kaczmarek, Krzysztof; Moch, Natalia (Roczniki Nauk Społecznych, 2026)
The article analyses non-kinetic operations as a tool used by Russia to exert strategic pressure on Western countries, with particular emphasis on Finland and Poland. The study covered three areas: the geopolitical context, the instrumentalization of migration, as well as cyberspace and the information environment. Our qualitative research methods, including analysis of secondary sources and strategic documents, comparative analysis and content analysis, demonstrated that non-kinetic operations are multi-layered and tailored to local conditions. Moreover, they achieve strategic goals without the use of military force. The effectiveness of these operations depends on the institutional and social resilience of states, and their consequences differ in Finland and Poland due to the different historical and geopolitical context.